1980
DOI: 10.2527/jas1980.504597x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Ewe Milk Production and Composition and Preweaning Lamb Weight Gain

Abstract: Thesis typed by Georgette Fosque for GLAFIRO TORRES-HERNANDEZ 2 respect to repeated observations on the same ewe. The correlation between subjective condition score and total milk production was -.25.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0
3

Year Published

1992
1992
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 34 publications
3
18
0
3
Order By: Relevance
“…Milk production increased with the size of the litter between single lambs and twins, in agreement with the results in other studies conducted in tropical regions [2,3,19]. Supplementing diets of Martinik ewes suckling twins resulted in a 50% increase in milk compared to the milk production from days 0 to 70 of 1245 g .…”
supporting
confidence: 91%
“…Milk production increased with the size of the litter between single lambs and twins, in agreement with the results in other studies conducted in tropical regions [2,3,19]. Supplementing diets of Martinik ewes suckling twins resulted in a 50% increase in milk compared to the milk production from days 0 to 70 of 1245 g .…”
supporting
confidence: 91%
“…The growth rate of the single reared lambs in this experiment was up to 150 g/day faster than multiple reared lambs in Period 1, but the advantage declined to ~48 g/day in Period 2. Torres-Hernandez and Hohenboken (1980) reported the superior growth rate of single over twin lambs decreased as lactation progressed, with their growth rates being the same by weaning. Peart (1967) reported that twin lambs from ewes on a high plane diet had growth rates equal to single lambs from 6 weeks of age and had greater intakes of solid food per unit of metabolic body size.…”
Section: Discussionmentioning
confidence: 99%
“…Birth weight and ADG were reduced in lambs born to nutrient-restricted ewes, even when lambs were offered an ad libitum milk replacer diet (Meyer et al, 2010b). Milk production by the ewe and intake by the lamb are highly and positively correlated to lamb ADG (Burris and Baugus, 1955;Torres-Hernandez and Hohenboken, 1980;Wohlt et al, 1984;Snowder and Glimp, 1991). Although not all concentrations of nutrients were affected by gestational nutritional plane, totals for all nutrients measured except for butterfat were reduced in milk from ewes that were nutrient restricted during gestation.…”
Section: Potential Impacts Of Milk Productionmentioning
confidence: 91%